Strategi Cina menghadapi “Malacca Dilemma” dalam Rangka Pengamanan Jalur Energy Cina di Selat Malaka - Suci Rahmadani; Heri Kusmanto; Warjio Warjio (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
As much as 80% of oil imports pass through this strait, while we know that industrialization in China is going very fast, and requires oil energy so that the industrial wheels continue to spin. This situation inevitably brought the Malacca Strait to the dilemma position of China (Malacca Dilemma). On the one hand, the Chinese government wants to reduce its dependence on oil imports through the strait given the vulnerability to sabotage, piracy and intervention from major countries (America and India), which have proxies in countries adjacent to the Malacca Strait. The theories used in this study are the theory of maritime strategy by Alfred T. Mahan, Sir Balford Mackinder's Geopolitical Theory, and the Balance of Power Theory of Nye. then the method used is a qualitative data analysis method. A series of steps to reduce dependence on the Malacca Strait is aggressively carried out by the Chinese government, such as Belt and Road Initiative (BRI), String of Pearls, Nine Dash Line, and Construction of the Kra Canal in Thailand. Facing this condition, it is also necessary to review Indonesia's position in the face of the complexity of the problems in the Malacca Strait in order to deal with the various maneuvers that took place in the Straits of Malacca.